Strategi Kebijakan Penguatan Ekoteologi di Kantor Kementerian Agama Kota Jakarta Barat - Warandi, Jamal Hasan (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes the issues at the Ministry of Religious Affairs Office in West Jakarta City, namely the Failure of Internal Waste Management and the Absence of Standard Operating Procedures (SOP). The purpose of writing this policy paper is to explain the waste management strategy at the Ministry of Religious Affairs Office in West Jakarta City to support the success of the Minister of Religious Affairs’ Priority Program for 2025 – 2029, specifically the second point, which is Strengthening Ecotheology. Using a qualitative method approach, this policy paper emphasizes descriptive analysis methods. Broadly speaking, the analysis results show that the main causes affecting waste management at the Ministry of Religious Affairs Office in West Jakarta City, based on the Fishbone Diagram, consist of four dimensions: resources, organization, internal factors, and external/regulations. The appropriate and urgent policy alternative that reflects effectiveness, efficiency, and suitability in supporting waste management at the Ministry of Religious Affairs Office in West Jakarta City is the Preparation and Implementation of Waste Management SOP. Therefore, the author concludes that this policy plays a significant role and needs to be implemented immediately. Based on the analysis results, the author recommends that the Head of the Ministry of Religious Affairs Office in West Jakarta City prepare and implement the Waste Management SOP.